1995
DOI: 10.3109/00365529509101602
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Attenuates the Hyperdynamic Circulatory State in the Gastric Mucosa of Rats with Portal Hypertension

Abstract: The significant reductions of gastric mucosal ISO2 and IHB by somatostatin support the hypothesis that somatostatin is capable of attenuating the hyperdynamic circulatory state in the gastric mucosa of rats with portal hypertension and may have a beneficial effect on portal hypertensive gastropathy. This hypothesis deserves to be evaluated in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…No studies have analyzed the efficacy of carvedilol, another nonspecific β-adrenergic receptor antagonist, in controlling bleeding from PHG [227] . Somatostatin and octreotide: Somatostatin and octreotide, a synthetic somatostatin analogue, cause splanchnic vasoconstriction, reduce portal pressure, reduce portal blood flow, and decrease gastric perfusion in animal models and in patients with PHG [105,106,160,[228][229][230][231] . For example, Chan et al [228] found octreotide infusion, compared to placebo, significantly increased systemic vascular resistance [3.4 ± 0.2 (SD) mmHg/mL per minute per 100 g vs 2.7 ± 0.2 (SD) mmHg/mL per minute per 100 g, P < 0.05], and significantly decreased portal pressure [9.9 ± 0.5 (SD) mmHg vs 12.5 ± 1.2 (SD) mmHg, P < 0.05] in cirrhotic rats.…”
Section: Pharmacotherapy For Phgmentioning
confidence: 99%
“…No studies have analyzed the efficacy of carvedilol, another nonspecific β-adrenergic receptor antagonist, in controlling bleeding from PHG [227] . Somatostatin and octreotide: Somatostatin and octreotide, a synthetic somatostatin analogue, cause splanchnic vasoconstriction, reduce portal pressure, reduce portal blood flow, and decrease gastric perfusion in animal models and in patients with PHG [105,106,160,[228][229][230][231] . For example, Chan et al [228] found octreotide infusion, compared to placebo, significantly increased systemic vascular resistance [3.4 ± 0.2 (SD) mmHg/mL per minute per 100 g vs 2.7 ± 0.2 (SD) mmHg/mL per minute per 100 g, P < 0.05], and significantly decreased portal pressure [9.9 ± 0.5 (SD) mmHg vs 12.5 ± 1.2 (SD) mmHg, P < 0.05] in cirrhotic rats.…”
Section: Pharmacotherapy For Phgmentioning
confidence: 99%
“…It has a half-life of 100 min compared to 2 or 3 min for somatostatin and can be administered both subcutaneously and intravenously. In animal models of portal hypertension, somatostatin has been shown to reduce GMBF [13]. Sung et al [13], using a rat model of portal hypertension, detected a significant decrease in mucosal hemoglobin saturation and hemoglobin concentration following the administration of somatostatin.…”
Section: Discussionmentioning
confidence: 98%
“…In animal models of portal hypertension, somatostatin has been shown to reduce GMBF [13]. Sung et al [13], using a rat model of portal hypertension, detected a significant decrease in mucosal hemoglobin saturation and hemoglobin concentration following the administration of somatostatin. They used reflectance spectrophotometry to measure gastric mucosal blood flow.…”
Section: Discussionmentioning
confidence: 98%
“…Prehepatic portal hypertension was induced by a well-described standard technique. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] An upper midline abdominal incision was made under aseptic conditions. The portal vein was isolated.…”
Section: Methodsmentioning
confidence: 99%
“…In rats with portal hypertension induced by partial portal vein ligation (PPVL), [1][2][3][4][5][6][7][8][9][10][11][12][13][14] there is an increase in splanchnic blood flow, 1,5,15 including gastric mucosal blood flow. 8,13,16 Reduction of the elevated portal pressure by ␤-adrenoceptor antagonists 1,10 in these rats is associated with a decrease in ethanol-induced gastric mucosal damage.…”
mentioning
confidence: 99%